Early Clinical Outcomes, Patterns of Failure, and Acute Haematologic Toxicity of Image-Guided Volumetric Modulated Arc Therapy (IG-VMAT) in the Definitive Treatment of Locally Advanced Carcinoma Cervix - Ahmad, Irfan (Clin Med Insights Oncol, 2018)
PURPOSE: To evaluate clinical outcomes and failure patterns in patients with locally advanced cervical cancer (LACC) treated definitively using image-guided volumetric-modulated arc therapy (IG-VMAT). METHODS AND MATERIALS: This retrospective review included 18 consecutively treated patients with LACC. Treatment consisted of IG-VMAT and concurrent chemotherapy followed by intracavitary radiotherapy. The primary end points were overall survival (OS) and disease-free survival (DFS). Acute haematologic toxicity was evaluated using Radiation Therapy Oncology Group (RTOG) criteria. RESULTS: A total of 16 patients were either stage IIB or IIIB and the median follow-up was 30.5 months (interquartile range: 13-36.25 months). The 2-year DFS was 63.3% (95% confidence interval [CI]: 52.8%-72.4%) and 2-year OS was 72.2% (95% CI: 62.1%-80.5%). There were 7 treatment failures, predominantly in-field. Acute haematologic toxicity was low. CONCLUSIONS: IG-VMAT is associated with favourable outcomes for patients with LACC.